Quick Solutions for Great Type Combinations / 100 Swipeable Solutions for Choosing Typefaces that will Look Great Together - and How to Create the Right Look for Your Clients - Buchanan Carol (1993)
This book offers design ideas for a wide variety of printed pieces through 100 swipeable designs that combine any two of sixteen classic typefaces. Introduction, About Type, Newsletters, Ads, Brochures, Letterheads, Special Applications, Using Display Type, Beyond the Rules, Index.